Role of epigenetics in mental disorders. - Stuffrein-Roberts S; Joyce PR; Kennedy MA (Australian & New Zealand Journal of Psychiatry, 2008)
The purpose of this paper was to selectively review the literature on the role of epigenetics in mental illnesses. Aberrant epigenetic regulation has been clearly implicated in the aetiology of some human illnesses. In recent years a growing body of evidence has highlighted the possibility that epigenetics may also play a key role in the origins and expression of mental disorders. Epigenetic phenomena may help explain some of the complexity of mental illnesses and provide a basis for discovering novel pharmacological targets to treat these disorders.